4X + Y  2z = 0
2X 3Y + 3Z = 9
6X  2Y + Z = 0
4X +Y  2Z = 0 0X + 7 Y  8Z = 18 4X + Y  2Z = 0 4X + Y 2Z = 0
2 ( 2X  3Y + 3Z = 9) 3(2X  3 Y + 3Z) = 9 4 ( 0X 11y +10Z = 27 ) 0X  9Y +0Z = 18
6X 2Y +Z = 0 6X 2Y + Z =0 5 ( 0X +7Y 8Z = 18) 0X +7Y 8Z = 18
4X + Y  2Z = 0 4X + Y 2Z = 0 4X +0 Y +0Z = 3
0X + Y + 0Z =2 0X + Y+ 0Z =2 0X + Y + 0Z = 2
0X + 0Y  8Z = 4 0X + 0Y +Z = 1/2 0X + 0Y + Z = 1/2
X = 3 Y = 2 Z = 1/2 are the answers:
Following procedure:
first eliminated X in both sides by multiplying 2nd equation by 2 and adding with first one
and 2nd equation by +3 and adding to 3rd one. The System reduces from 3 equation to 2 , and solve
then Y, and Z will be substituted to 1st equation and value of X will be calculated.
5/6/2014

Parviz F.